Can protest movements influence the (re)formulation of public policies? Analysis of the recent controversial reform of the Portuguese public maternal health services - Matos, Ana Raquel (2010)
The present work attempts to counter the restricted view about citizen participation and points out its relevance in public policies (re) formulation. In order to do that, it will focus on protest actions occurred in 2006 and 2007, in Portugal, motivated by the decision of the Health Ministry to close several maternity wards. Based on the analysis of the arguments advanced by the political power, reasoned on a report elaborated by an expert group and on the analysis of the popular reactions during the protests, this article offers an analysis of the geography of the protests. It also evaluates the capacity of the popular movements to participate in the decision process as well as the political empowerment emerging from this form of collective action.